NUTRITIONAL AND ANTI-OXIDANT QUALITY OF PAP FLOUR PREPARED WITH DIFFERENT MIXES OF ORANGE FLESHED SWEET POTATO, MAIZE, AND SORGHUM. - OJELEYE, A. E.; AFOLABI, M. S; OLALEKAN, K. K.; ADEDIRE, A.O.; AKORODA , M. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
Fermented cereal porridge, is a popular cereal in Nigeria and most West Africa. It is also called ‘pap’ and is usually made from corn (Zea mays) and sorghum (Sorghum vulgare). Sweet potato (Ipomea batatas) especially the orange fleshed (OFSP) can be used to fortify most cereal and starch foods. This study was carried out to analyze the nutritional quality of different traditional pap flour mixes; 50% Maize + 50% OFSP; 50% Sorghum + 50% OFSP, 50% Sorghum + 50% Maize, 100% Maize and 100% Sorghum. The grains were picked by removing the dirt, washed and dried till constant weight while fresh OFSP roots were washed, sliced and dried until constant weight was obtained. Data were collected on the pap flour mixes to analyze the proximate quality, mineral composition and selected anti-oxidants. Data collected were analyzed using SPSS while means were separated using Duncan Multiple Range Test. Result showed that addition of 50% OFSP to 50% Maize improved the potassium (261.30mg/100g) and crude protein (9.92g/100g) while 50% Sorghum + 50% OFSP had better calcium (7.69 mg/100g), lutein (12.59 µg/100g), Zeaxanthin (8.31 µg/100g) and beta-carotene (172.86 µg/g). Result also showed that there was no significant difference (p≤0.05) in the dry matter content of the different pap flour mixes. Conclusively, traditional flour mix with OFSP are higher in crude protein, lutein, zeaxanthin and beta-carotene. Therefore, 50% Maize + 50% OFSP and 50% Sorghum + 50% OFSP pap flour mix should be promoted, to enhance its potassium, crude protein, zeaxanthin, carotene and lutein content.